Temporal and Spatial Evolution Mechanisms of the Water-Conducting Fractured Zone of Overlying Strata in the Kongzhuang Coal Mine - Zhang Pei-ding; Sun Chao-shang; Fan Xuan; Li Song-tao; Wang Long-jing; Cao Zheng-zheng (Geofluids)
Kongzhuang coal mine of Shanghai Datun Energy Resources Co., Ltd. is a typical deep coal mine in eastern China. The mining disturbance of working face in deep coal mine leads to the fracture and movement of overlying strata and the damage of the aquifer in overlying strata, thereby causing water inrush disaster and posing a serious threat to the safety production in coal mine. Therefore, the temporal and spatial evolution mechanism of the water-conducting fractured zone of overlying strata in the Kongzhuang coal mine is researched systematically in this paper. Especially, the hydro-geological conditions and mining conditions in the Kongzhuang coal mine are analyzed; on this basis, the fracture and movement of overlying strata are simulated by physical similarity simulation test, and the temporal and spatial evolution rule of overlying strata in the Kongzhuang coal mine is obtained. Besides, the development height of “two zones” is measured by double-end water shutoff detection method, and the risk assessment for the water inrush disaster of the coal seam roof is carried out in the Kongzhuang coal mine. The research achievements in this paper indicate that the water-conducting channel formed in the mining process of #7 coal seam is the most important water-filling channel. Quaternary aquifer water recharges the mine indirectly through the bedrock aquifer, and the sandy mudstone with large thickness is the key layer to control the development of a water-conducting fracture zone. Meanwhile, the height of the caving zone is 26.7 m, about 8.3 times of mining height, and the height of the fracture zone is 68.3 m, approximately equal to 16.26 of the mining height. The results of #1 and #2 borehole leakages in the double-end water shutoff detection method show that the height of the water-conducting fractured zone is 63.70 m-65.27 m, and the split-to-mining ratio is 15.17-15.54. The water inrush risk of the coal seam roof shows that most of the 7436 working face is in the transition zone, and a small area around the cutting hole of the working face is in the relatively dangerous zone. Therefore, the innovation of this paper is that the temporal and spatial evolution mechanism of the water-conducting fractured zone of overlying strata in the Kongzhuang coal mine is revealed, which provides the theoretical guidance for the prediction and prevention of water inrush disaster in the coal mine with the similar mining conditions.